The Relationship Between Prevalence of Antibiotics Resistance and Virulence Factors Genes of MRSA and MSSA Strains Isolated from Clinical Samples, West Iran - Arabestani, Mohammad Reza (Oman Med J, 2018)
OBJECTIVES: We sought to evaluate the relationship between the prevalence of antibiotics resistance and virulence factors genes in methicillin-resistant Staphylococcal aureus (MRSA) and methicillin-sensitive S. aureus (MSSA) strains from clinical samples taken in west Iran. METHODS: We performed a cross-sectional study using 100 MRSA and 100 MSSA samples isolated from clinical specimens. We used biochemical methods to identify the isolates, which were confirmed by the polymerase chain reaction (PCR) assay. Antibiotic susceptibility testing was performed using disk diffusion. PCR detected the presence of virulence factors, including enterotoxin genes, toxic shock syndrome toxin-1 (TSST-1), and exfoliative toxin. RESULTS: The majority of MRSA isolates exhibited a high level of resistance to common antibiotics and susceptible to vancomycin, while most MSSA isolates were also resistant to erythromycin and ciprofloxacin. The prevalence of Staphylococcal enterotoxins (SEs) were reported 147 (73.5%). Among 100 MRSA samples, 92 (92.0%) harbored SAg genes. The most frequent toxin gene was sea (45.0%) followed by sec (39.0%). Among 100 MSSA isolates, 89 (89.0%) harbored SAg genes and the most prevalent genes were sea (42.0%), sek (38.0%), sec (35.0%,), and TSST-1 (10.0%). The prevalence of TSST-1 and exfoliative toxin genes in MRSA samples were 12 (12.0%). The association of SAg genes with MRSA and MSSA isolates showed a high prevalence of enterotoxin seq, seg, and sei in MRSA than MSSA with a statistically significant difference (p < 0.050). CONCLUSIONS: The prevalence of MRSA and the association of pathogenic agents with antibiotics resistance genes can lead to the emergence of strains with higher pathogenicity and less susceptibility.